A Confluence of Anticolonial Pathways for Indigenous Sacred Site Protection. (1st June 2020) - Ellis, Rachel; Perry, Denielle
Abstract: The confluence of the Little Colorado and Colorado Rivers is an Indigenous socio‐ecological landscape, revolving in large part around water resources. Substantial surface and groundwater use within the Little Colorado River (LCR) basin threatens the water sources of the confluence, springs in the LCR basin, and specifically the Hopi Sipapuni —a sacred site of cultural emergence. To address concerns about diminished flows of sacred springs, we engaged in praxis through collaborative, reciprocal, community‐based research processes. Through the lens of anticolonial theory, we ask: Can federal policies be employed in an anticolonial pursuit of water and sacred site protection? How do Indigenous grassroots organizers envision protection and work to re‐Indigenize water management? Semi‐structured interviews with Indigenous community organizers and federal land managers were coupled with policy analysis of the National Historic Preservation Act/Traditional Cultural Properties, the ongoing LCR Adjudication, and the Treaty of Guadalupe Hidalgo. Findings point to multifaceted, complex, and contradictory themes that elucidate the continued influence of colonization on water governance and the degree to which protection solutions can be anticolonial. Criteria were generated for anticolonial protective pathways that highlight the centrality of reciprocal relationships, Indigenous Knowledges, and meaningful inclusion. While details about protection pathways for the confluence and Sipapuni are many, the salient finding is that the struggle for water protection in the LCR is the struggle for protection of inherent Indigenous rights.